2011
DOI: 10.1002/pen.22122
|View full text |Cite
|
Sign up to set email alerts
|

Liquid crystalline and photocrosslinkable poly(4,4′‐stilbeneoxy) alkylarylphosphates

Abstract: Three series of liquid crystalline and photocrosslinkable poly(4,4 0 -stilbeneoxy) alkylarylphosphates were synthesized from various 4,4 0 -bis(m-hydroxyalkyloxy)stilbenes (m ¼ 2, 4, 6, 8, 10) and arylphosphorodichloridates in chloroform by solution polycondensation method. Polarized optical microscope (POM) and differential scanning calorimetry (DSC) observations revealed that polymers containing less than four methylene spacer groups did not exhibit liquid crystalline (LC) texture, possibly due to smaller m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…These clearly indicated that dimerization occurred between the olefinic double bonds of the polymeric chain which involved 2π + 2π cycloaddition that formed a cyclobutane ring. This ring formation destroyed the conjugation of the π‐electrons and thus caused a decrease in the absorption maxima of the π–π* transition with a concomitant in the absorbance at a shorter wavelength which was due to single bond formation from the cyclobutane ring . The intensity of the absorption band at 335.5 nm gradually decreased until the irradiation time reached 1400 s when maximum photocrosslinking was achieved.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These clearly indicated that dimerization occurred between the olefinic double bonds of the polymeric chain which involved 2π + 2π cycloaddition that formed a cyclobutane ring. This ring formation destroyed the conjugation of the π‐electrons and thus caused a decrease in the absorption maxima of the π–π* transition with a concomitant in the absorbance at a shorter wavelength which was due to single bond formation from the cyclobutane ring . The intensity of the absorption band at 335.5 nm gradually decreased until the irradiation time reached 1400 s when maximum photocrosslinking was achieved.…”
Section: Resultsmentioning
confidence: 99%
“…The extent of photocrosslinking was evaluated by calculating the photocrosslinking percentage of the photoreactive olefinic chromophore. Polyesters PTI1 − PTI5 showed an increase in the percentage of photocrosslinking followed by a plateau where the photocrosslinked network resisted further reaction subsequent to the exposure of UV light . PTI1 − PTI5 achieved a maximum percentage of photocrosslinking (77% − 80%) after 1400 s of UV irradiation and showed no significant effect from an increase in flexible alkyl chain length.…”
Section: Resultsmentioning
confidence: 99%
“…This behavior clearly indicated that dimerization occurred in the olefinic double bond of the polymeric chain which involved 2π+2π cycloaddition in forming a cyclobutane ring. This ring formation destroyed the conjugation of the π‐electron system thus giving a decrease in the absorption maxima of π–π* transition with a concomitant in the absorbance at a shorter wavelength which was because of the single bond formation from the cyclobutane ring . PAI1‐PAI5 reacted photochemically similar to cinnamic acid and its derivatives where a cyclobutane structure was formed after the cross‐linking .…”
Section: Resultsmentioning
confidence: 99%
“…All of these polyesters showed steady increase in the percentage of photocrosslinking followed by a plateau. PAI1 ‐ PAI5 achieved maximum percentage of photocrosslinking (70–72%) at 1300 s indicated that the formation of photocrosslinked network resisted further subsequent exposure to UV light after 1300 s . The formation of cyclobutane ring in the polymer backbones causes steric hindrance because of the bulkiness of the structure and thus hinders the ability of the ‐C=C‐ moieties to cross‐link completely …”
Section: Resultsmentioning
confidence: 99%